The power of live engagement : How brand experiences and e-WOM drive Somethinc’s Tiktok sales - Safina Nashwa Haliza; Rita Komaladewi (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study examines the influence of brand experience and electronic word of mouth (eWOM) on purchase intention in the context of TikTok live streaming conducted by Somethinc. As live-streaming commerce continues to transform consumer engagement in the digital beauty industry, understanding the factors that drive purchase intention has become increasingly important for brand competitiveness and customer acquisition. Employing a quantitative approach, the study analysed the relationships among variables using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS. Brand experience was evaluated through sensory, emotional, behavioural, and intellectual dimensions, while eWOM was assessed based on information usefulness, attitudes toward information, and information credibility. Purchase intention was measured through indicators related to purchase certainty and behavioural tendencies toward buying. The findings reveal that both brand experience and eWOM exert positive and significant influences on purchase intention. An engaging and informative brand experience enhances consumer perceptions and emotional connections with the brand, while credible and useful eWOM strengthens trust and confidence in purchasing decisions. These results suggest that interactive live-streaming activities, supported by authentic consumer-generated information, play a critical role in stimulating purchase intention among digital consumers. The study contributes to the growing literature on social commerce, digital marketing, and consumer behaviour by providing empirical evidence from the rapidly expanding live-streaming ecosystem within Indonesia’s beauty industry. Keywords: Brand Experience; eWOM; Purchase Intention; TikTok; Live Streaming; Somethinc